Fin whale (Balaenoptera physalus) age estimate validated through bomb radiocarbon dating - Sigríður Vala Finnsdóttir 1997- (2023)
Information on age is often used to calculate important biological variables such as growth rate and productivity, hence, inaccurate age estimates can lead to the mismanagement of exploited species and threaten their survival. There are no methods for ageing baleen whales for which ageing accuracy has been confirmed. Fin whale (Balaenoptera physalus) age is usually estimated by counting growth increments found in their earplugs, with the general assumption that one growth increment is deposited annually. Here I report the first validation of annual growth increment formation in fin whale earplugs using bomb radiocarbon dating. Radiocarbon assays of growth increments formed in fin whales harvested in 2013 revealed that bomb radiocarbon had been incorporated and preserved in their earplugs. The fin whale radiocarbon chronology aligned well with published marine reference chronologies where the year of formation was known and confirmed that earplug growth increment counts provide an accurate estimate of fin whale age. Growth increment δ13C values indicated a metabolic and dietary carbon source, hence the timing and magnitude of the radiocarbon peak value can be attributed to water mixing rates in the regions which the fin whale’s prey inhabit. There was no bias when comparing eleven age estimates made by two readers, and there was no consistent difference between the left and right earplugs from eight fin whales. Although the age validation reported here was based on a small sample size, the results confirmed the annual formation of earplug growth increments, thus supporting the continued use of earplug growth increment counts for determining fin whale age. Aldur lífvera er oft nýttur til þess að reikna mikilvægar líffræðilegar breytur eins og vaxtarhraða og frjósemi. Þar af leiðandi getur ranglega áætlaður aldur orsakað óstjórn veiða og ógnað tilvist tegunda. Áreiðanleiki í aldursgreiningu skíðishvala hefur ekki verið staðfestur fyrir neina aldursgreiningar aðferð. Aldur langreyða (Balaenoptera physalus) er ...